Pelaksanaan Pembelajaran Daring Melalui Zoom Meeting Kelas IV Sekolah Dasar - Samsiah Samsiah; Deni Setiawan; Edi Waluyo (Jurnal Ilmiah Wahana Pendidikan, 2023)
this study aims to describe the implementation of online learning using the zoom meeting application for fourth grade elementary school students during the covid-19 pandemic. The research method used by the author is descriptive research method. Research participants consisted of students and teachers of grade IV Elementary School. Data collection techniques in the form of study documentation, questionnaires and interviews. Data analysis techniques in this study used qualitative data analysis techniques and quantitative data analysis techniques. Qualitative data analysis techniques have three streams of activities simultaneously, namely; Data Reduction, Data Presentation and Data Inclusion. While the quantitative data analysis techniques. use presentation. The results showed that the learning design made by the teacher was good. The interaction of teachers and students based on the results of the questionnaire 100% went smoothly. The supporting factors of the facilities are already supportive, the teacher has prepared the lesson well, the support from the parents and the enthusiasm of the students to take part in the learning. The inhibiting factor is sometimes the internet network is not good, teachers must be more creative in choosing learning media, there are some parents who have to work so they can't accompany their children, students get bored easily if learning is just like that. The value of learning outcomes obtained by students is good, the average value of students has exceeded the KKM.